Earlier biomarkers in fish evidencing stress responses to metal and organic pollution along the Doce River Basin - Yamamoto, F. Y. [UNESP]; Onishi, K. [UNESP]; Ralha, T. R. [UNESP]; Silva, L. F.O.; Deda, B.; Pessali, T. Y.C.; Souza, C.; Oliveira Ribeiro, C. A.; Abessa, D. M.S. [UNESP] (Elsevier, 2023)
The Doce River Basin (DRB) represents a well-described watershed in terms of contamination by metals, especially after a major environmental disaster of a mining tailing dam failure. Despite the massive mortality of the ichthyofauna, very few studies addressed the risks to the health of wild fish exposed to complex mixtures of pollutants from multiple sources. The present study proposed to investigate earlier responses of fish for assessing the impacts of multiple sources of pollution, considering: different niches of fish and target organs; and the influence of seasonality, associated with their probable sources of pollution. To achieve that, fish were collected along the DRB, and biomarkers responses were assessed in target organs and correlated with the levels of inorganic and organic contaminants. As one of the most prominent responses, fishes from the Upper DRB showed the highest expression of the metallothionein and oxidative stress parameters which were related to the higher levels of metals in this region due to the proximity of mining activities. On the other hand, higher levels of DNA damage and increased AChE activity from fish sampled in the Mid and Lower DRB were more associated with organic contaminants, from other sources of pollution than mining residues. The integrated biomarker responses also revealed seasonal variations, with higher values in fishes from the dry season, and pelagic fish showing greater variation within the seasons. The multivariate analysis integrating suitable biomarkers with chemical data represented an adequate strategy for assessing the ecological risks in the DRB, allowing the identification of distinct spatio-temporal impacts from multiple sources of contaminants. The continued exposure of the ichthyofauna representing future risks reinforces the need for ecological restoration and the protection of the fauna from the Doce River.
Keywords: Biochemical biomarkers; Complex mixtures; Iron tailing waste; Multiple pollution sources; Multivariate analysis; Native adult fish